Pengembangan Desain Pembelajaran Dengan Model Contextual Teaching and Learning (CTL) Pada Pelajaran Agama Islam (Pai) Di Kelas VII SMP Negeri 2 Ngawi - Sugiharto; Samsul Hadi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
With regard to the development of basic and applied concepts of Islamic Religious Education in the future, there are two important things. First, spreading Islamic religious education as a basic and applied concept. The basic concept of Islamic Religious Education contained in the Qur'an and Al-Hadith is a normative teaching, so when studying Islamic Religious Education in Indonesia it means studying the applied normative teachings on Education in Indonesia, secondly, about the focus of study and development. This is important to be cleared to provide a clearer portrait of the continuity of Islamic Religious Education, so that creative people, often experiment ideas, and can design quality educational institutions for the development of Islamic education in the future. The research method used is R&D by determining the Steps: Preliminary Study, Planning, Developing Initial Product, initial trial, Revision to compile the main product, Main field test, Revision to compile operational products, Trial for operational products, Final Product Revision, Desimination and Implementation of Development product results. From the results of this research it can be concluded that by preparing a learning design with the CTL model on Islamic Religious Education Lessons Implementation of Learning design development with CTL model in Islamic Religious Education class VII class 2 Ngawi state junior high school is developed in four stages, namely: 1) Conduct a need assessment, 2) design and develop the initial product with regard to the principles of learning design development and learning design elements, 3) conduct field trials, but before conducting trials, the product is validated by experts, 4) evaluation and revision of learning design. The results of this development can be used as a reference and reference in the process of designing learning with the CTL model in Islamic religious education class VII state junior high school 2 semesters in particular and other public and private junior high schools that have the same characteristics in general.